Learning space design preferences of hearing impaired students in Davao City - Nagal, Cristine Jil B. (2020)
The study was conducted to create solutions in developing learning spaces for the hearing impaired students in Davao City. Deaf people inhabit a rich sensory world where vision and touch are a primary means of spatial awareness and orientation. Our built environment, which is largely constructed by and for hearing individuals, presents a variety of surprising challenges to which deaf people have responded with a particular way of altering their surroundings to fit their unique ways of being. This manipulation of the spaces by the hearing impaired individuals created a way to develop the Deaf Space Design Guidelines by the Gallaudet University which is the center of this study. The study revolves around the five principles of Deaf Space which are: space and proximity, mobility and proximity, sensory reach, light and color, and acoustics. It involves a community-based participatory research consisted of four main qualitative methods (1) non-participant observation, (2) visual analysis, (3) visual focus group and (4) collective analysis. The respondent consisted of hearing impaired students from fourth grade to senior high school level and from three participating schools (Davao City Special National High School, Davao City Special School and Deaf Ministries Institute, Inc.). The results showed that Light and Color concept ranked first in the preferred concept by the hearing impaired students followed by Mobility and Proximity, Space and Proximity, Sensory Reach and Acoustics. Though the concepts often overlap one another, the results proved how Light and Color enhances the visually centered perspectives of the hearing impaired students and how important creating visual communication is to them. But this doesn?t mean that other concepts were valued less rather, it shows what they can easily recognized with the spaces they have and the spaces that were presented to them. It is important to note that the concepts are interrelated and overlaps one another thus each enhances one another creating a much more functional learning spaces for the HI students. The Deaf space approach is only starting to reveal its potential, and the guidelines are a work in progress rather than a set of proven rules. The study of deaf space offers valuable insights about the interrelationship between the senses, the ways we construct the built environment and cultural identity from which society at large has much to learn from.